HUBUNGAN ANTARA BUDAYA ORGANISASI DENGAN KOMITMEN ORGANISASI PEGAWAI NEGERI SIPIL DINAS KEHUTANAN PROVINSI KALIMANTAN TIMUR - Kurnia, Fajar (MOTIVASI, 2013)
This study aims to determine whether there is a significant relationship between organizational culture and organizational commitment of civil servants so that there are two relationships that will be investigated in this study, namely: 1) organizational culture, 2) organizational commitment.The study was conducted at Civil Servants East Kalimantan Provincial Forestry Office by the number of research subjects as many as 152 people with visitors specifications of men and women, average age 30 years to 50 years with a wide variety of educational backgrounds.Data analysis was performed using SPSS (Statistical packade for Social Science) 13 for Windows. Results of hypothesis testing using Spearman Rank analysis (R) of - 0.117, p equal to 0.246, and 0.265 t of t table (two-way) 0.05 = 1.99. This means that a significant level of 0.05, it can be concludedÂ  that there is no relationship between organizational culture and organizational commitment Civil Servants East Kalimantan Provincial Forestry Office.